Historical and interpretative aspects of quantum mechanics: a physicists’ naive approach - Berche, B.; Chatelain, C.; Dufour, C.; Gourieux, T.; Karevski, D. (Condensed Matter Physics, 2006)
Many theoretical predictions derived from quantum mechanics have been confirmed experimentally for the last 80 years. However, interpretative aspects have long been subject to debate. Among them, the question of the existence of hidden variables is still open. We review these questions, paying special attention to historical aspects, and argue that one may definitively exclude local realism based on the present experimental outcomes. Nevertheless other interpretations of Quantum Mechanics are not excluded.